Застосування штучного інтелекту для створення інтерфейсів мобільних додатків - Пучка, Г. С. (ХНУРЕ, 2024)
Galileo AI, a cutting-edge neural network designed for generating mobile app and website interface designs, marks a significant leap forward in the fieldof generative design. Harnessing the power of artificial intelligence, it streamlines and accelerates the creative process for designers and developers alike. The network's versatility allows users to create interfaces based on textual prompts or uploaded images, with results generated in just minutes. Integrated with the popular Figma editor, Galileo AI provides a seamless workflow for refining and editing generated layouts. The tool's democratized pricing and various plans cater to both seasoned professionals and newcomers, making it a pivotal player in the design industry's evolution.
Keywords: мобільний додаток; створення інтерфейсів